Engineering maintenance management - Niebel, Benjamin W. (Industrial engineering, 1994)
Covering the fundamental theories, principles, and proven techniques of successful quality engineering maintenance management programs, this outstanding reference furnishes all levels of engineering management with the material necessary to provide cost-effective maintenance - discussing the functional design of products as well as the identification of failure systems that permit scheduled maintenance procedures.